Single Nucleotide Polymorphisms associated with alimentary fatty liver disease are not genetic risk factors for treatment-associated hepatic steatosis in HIV patients on HAART - Dold Leona; Berger Cordula; Luda Carolin; Boesecke Christoph; Schwarze-Zander Carolynne; Nischalke Hans-Dieter; Wasmuth Jan-Christian; Kurt Rockstroh Jürgen; Spengler Ulrich (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Analyzing SNPs linked to fatty liver disease, this study finds no association with HAART‑related hepatic steatosis in HIV patients. The work underscores the multifactorial nature of antiretroviral toxicity and points to metabolic and pharmacologic contributors beyond common variants.
Keywords: HIV